2017
DOI: 10.4103/0259-1162.186596
|View full text |Cite
|
Sign up to set email alerts
|

Financial implications of intravenous anesthetic drug wastage in operation room

Abstract: Background and Objectives:Anesthetic drugs and material wastage are common in operation rooms (ORs). In this era of escalating health-care expenditure, cost reduction strategies are highly relevant. The aim of this study was to assess the amount of daily intravenous anesthetic drug wastage from major ORs and to estimate its financial burden. Any preventive measures to minimize drug wastage are also looked for.Methods:It was a prospective study conducted at the major ORs of a tertiary care hospital after gettin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
0
21
1
Order By: Relevance
“…In addition, the use of drugs in anesthesia creates a great cost. At this point, cost effectiveness can be achieved by reducing the doses of the drugs (29). In our study, the consumption of the inhalation agentwhich attracts attention with its increasing price and the consumption of opioids-which have relatively side effects and which increased the cost due to the subsequent abuse, were found to be lower.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, the use of drugs in anesthesia creates a great cost. At this point, cost effectiveness can be achieved by reducing the doses of the drugs (29). In our study, the consumption of the inhalation agentwhich attracts attention with its increasing price and the consumption of opioids-which have relatively side effects and which increased the cost due to the subsequent abuse, were found to be lower.…”
Section: Discussionmentioning
confidence: 61%
“…Atropine and ephedrine accounted for 12% and 2.1% of wastage of at the end of the workday total cost loss in this study. In previous studies, significant wastage was reported for atropine and ephedrine ( 2 , 9 ). In each operating room, ephedrine 50 mg and atropine 1 mg were routinely prepared as emergency drugs.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, rocuronium (29.95%) caused the most cost loss. In another study, vecuronium (35.21%) caused the most financial loss ( 2 ). This loss can be reduced by appropriate use of neuromuscular blockers, assessment of the degree of blockage and loading of only the required amount.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations